Концепт «самотність» у поетичній мовотворчості кінця ХХ – початку ХХІ століття - Козловська, Л.; Дядченко, Г. (Культура слова, 2021)
У статті здійснено аналіз вербалізаторів концепту «самотність» у мові української поезії кінця ХХ – початку ХХІ століття. Доведено його важливість як компонента лінгвопсихологічного портретування людини-сучасника. Простежено
актуальні для поетичного моделювання стану самотності мовообрази із просторовою, кількісною та аудіальною семантикою. Наголошено, що конкретизація абстракту «самотність»
активно відбувається в семантичних площинах «природа» і
«побут», зі зниженням оцінності в останньому сегменті. Продуктивність окреслених напрямків образотворення підтверджують персоніфіковані структури з лексичним центром «самотність».
Серед інших показових засобів схарактеризовано образні
сполуки-описи психоемоційного стану самотності, розгорнуті
до рівня мікротексту. Відзначено, що проаналізовані образні структури засвідчують підвищену увагу сучасних авторів до словесно-художнього окреслення стану самотності. The article is devoted to the linguistic description of the concept
“loneliness” in the language of the Ukrainian poetry at the end of
ХХ – beginning of ХХІ centuries. The authors prove that «loneliness
» concept is a productive instrumentation of lingual depiction
of the psychological portrayal of a contemporary. Language of the
poetic works at the end of ХХ – beginning of ХХІ centuries gives
a convincing evidence to this statement. It represents such lingual
signs of the “loneliness” leitmotif as the abstract nouns loneliness,
solitude, fragmentation, loner, sad and lonely, recluse, away from
everyone, epithets lonely, lone, reclusive, deserted.
In process of the artistic modelling of the state of loneliness
the lingual images with the space, quantity or the auditory semantics
are used. In the language of the Ukrainian poetry at the end of
ХХ – beginning of ХХІ centuries such line of the imaginary creation
is accompanied with the associates fold, circle, labyrinth, wall,
home, room, barrier, etc. They are functioning as the components
of the imaginative structures of the different degree of extension.
It may be two-componential genitive metaphor or vast metaphoric
descriptions which are the components of the predicative metaphor.
Suffering of the lonely person are expressively depicted in the poetic
contexts united with the quantitative meaning. Such meaning
is typical for the numerals and adjectives (big) or adverbs (to overflowing).
Semantic field created around the nomination loneliness provides
an indication of such trend of the modern lingual creativity
as gradual concretization of the abstract loneliness. In such process
the associative halo changes its emotional and evaluative marking.
However, the associative parallels with the world of nature usually
have general positive connotation and the object associations are
the factors of the context domestication together with the connotation
change. During the abstract “loneliness” concretization demotion
of the poetic statement also takes place. Sublime tone and
evaluation are episodic while the object associations are the lingual
symbols of the domestic or ironic colour. The efficiency of such
imaginative line is asserted by the personifying structures with the
lexical centre “loneliness”. We’d like to note that during the nearing
to the concretization loneliness abstract develops its own epithet
field of colours. Latter are mainly eligible or achromatic nominations.
Among the other characteristic poetic phenomena is modelling
of the imaginative structures meaning the psychological state
of loneliness extended to the micro text level.
The lingual material analysed makes possible to come to the
conclusion of the importance of the loneliness concept in process
of the psychological portrayal of the contemporary. The imaginative
structures observed prove the importance of the philosophical
reflection and poetic depiction of the problem of loneliness in the
modern world.